The Impact of Service Quality and Electronic Service Quality on Customer Satisfaction and Customer Loyalty: A Study on The Customers of Bank Central Asia - Saskia Deffa Febriend; Annisa Rahmani Qastharin (Mandalika Institute, 2024)
The Indonesian banking sector is facing increasing competition due to the rise of digital banks. This has led to evolving customer preferences, with a growing demand for seamless digital banking experiences. While BCA has a strong market position, it faces complaints regarding its mobile banking app, M-BCA, particularly concerning user interface and experience, which indicates potential issues with service quality and electronic service quality. The need to understand the factors influencing customer satisfaction and loyalty in this changing landscape are growing from conventional banks, like BCA. This study investigates the impact of SERVQUAL and e-SERVQUAL on customer satisfaction, electronic customer satisfaction and loyalty among BCA customers in Indonesia, which aims to address the challenges faced by conventional banks in the face of increasing competition from digital banks. A quantitative research approach was employed, involving a survey of 210 Gen Z and Gen Y BCA customers in Jabodetabek and Bandung. Data analysis was conducted using descriptive statistics and Partial Least Squares Structural Equation Modelling (PLS-SEM). The results confirm that both SERVQUAL and e-SERVQUAL significantly and positively influence customer satisfaction, which in turn strongly influence customer loyalty. However, e-SERVQUAL does not have a direct impact on customer loyalty, suggesting a more complex relationship. While digital services are increasingly important, traditional service quality remains a key driver of customer loyalty. The findings underscore the importance for conventional banks like BCA to maintain high service quality standards first and later continuously improve digital offerings to remain competitive in the digital age.